2018
DOI: 10.22159/ajpcr.2018.v11i7.25580
|View full text |Cite
|
Sign up to set email alerts
|

Treating Cervical Cancer With Herbs: A Review

Abstract: Medicinal plants have been on the forefront where research on the anticancer agent is planned. This review mainly focuses on several such as medicinal plants Rosmarinus officinalis, Solanum nigrum, Kaffir lime, and Garcinia nujiangensis used in the treatment of cervical cancer and the secondary metabolites derived from different plant sources. Plant molecules such as cisplatin, curcumin (-)- epigallocatechin (EGC)-3-gallate, EGC, epicatechin- 3-gallate, and other catechins that have a wide range of biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Polyphenols can curb the progression of aggressive tumors by inhibiting DNA synthesis and cell growth and by inducing apoptosis [23]. Visa et al's in vitro study demonstrated for the frst time that olive leaf extract may improve cervical cancer, which is mainly caused by HPV [24].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols can curb the progression of aggressive tumors by inhibiting DNA synthesis and cell growth and by inducing apoptosis [23]. Visa et al's in vitro study demonstrated for the frst time that olive leaf extract may improve cervical cancer, which is mainly caused by HPV [24].…”
Section: Introductionmentioning
confidence: 99%
“…1 Cervical cancer is a major health problem worldwide and the most common malignant tumor among women. 2 Chemotherapy is a method commonly used in cancer treatment. However, their high toxicity rate among the both of normal and cancer cells is the lack of desired eff ect of current therapies.…”
Section: Introductionmentioning
confidence: 99%